2013
DOI: 10.1097/yco.0b013e328361e7ae
|View full text |Cite
|
Sign up to set email alerts
|

Guideline implementation strategies for specialist mental healthcare

Abstract: Current knowledge about how guidelines should be implemented is still sparse and inconclusive in mental healthcare. Future studies should attempt to employ more rigorous designs, including random allocation of patients or clusters of patients, to shed further light on this compelling issue. Research on guideline implementation strategies should additionally take into account potential barriers to knowledge translation, which can heavily influence the implementability of treatment recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…They showed trends towards improvement in process and patient outcomes following guideline implementation [28]. This supports the legitimacy of CPG development and implementation in LMICs as one of a number of possible tools to approach scale up of mental health care in these settings.…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…They showed trends towards improvement in process and patient outcomes following guideline implementation [28]. This supports the legitimacy of CPG development and implementation in LMICs as one of a number of possible tools to approach scale up of mental health care in these settings.…”
Section: Introductionmentioning
confidence: 68%
“…A recent systematic review concluded that there was sufficient evidence from high income countries to view CPGs in mental healthcare as an essential asset if appropriately developed and implemented [28]. They showed trends towards improvement in process and patient outcomes following guideline implementation [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous authors have highlighted the increasing role of clinical practice guidelines in both physical and mental healthcare over the last two decades (e.g., Franx, ; Girlanda, Fiedler, Ay, Barbui, & Koesters, ; Grimshaw et al, ; Nathan, ; Parry, Cape, & Pilling, ; Pilling, ; Woolf, Grol, Hutchinson, Eccles, & Grimshaw, ). Parry et al () suggested that ‘health care professionals are living in the age of evidence‐based guidance’ (p. 337), highlighting a ‘remarkable proliferation of clinical practice guidelines’ (p. 337).…”
mentioning
confidence: 99%
“…What effects do guideline dissemination and implementation strategies have on process and patient outcomes, i.e., on clinician behaviour and treatment outcome at the patient level? A number of papers have investigated the effects of mental health guidelines being implemented, and the results suggest that: (a) if any effects on provider performance or patient outcome are mostly moderate and temporary; (b) studies with positive outcomes used complex multifaceted strategies or specific psychological methods to implement guidelines; (c) our current knowledge about how guidelines should be implemented is sparse and inconclusive in mental health care; (d) future studies should attempt to employ more rigorous designs; (e) research on guideline implementation strategies should take into account potential barriers to knowledge translation; and (f) randomised controlled trials, controlled clinical trials and before-and-after studies comparing guideline implementation strategies v. usual care have not shown consistent positive effects of guideline implementation on provider performance, but a more consistent small to modest positive effect on patient outcomes (Weinmann et al 2007;Girlanda et al 2013Girlanda et al , 2016. This latter finding suggests that guideline implementation strategies may have affected aspects of clinician behaviour that were not measured in controlled trials and that effects on patient outcome may have come about through mechanisms that have hitherto escaped the attention of researchers.…”
Section: Guidelines and Guideline Implementationmentioning
confidence: 99%